(untitled) (Revista de Ciências Agroveterinárias, 2023)
The study of chemical and biochemical aspects associated with the development of different plant parts enables the assessment of a series of reactions leading to the production of biomass and grain culture. Thus, the objective of was to study the difference in nitrogen efficiency in roots and shoots of two corn genotypes in the initial stages of plants growth, and evaluate the biochemical and physiological responses of these organs, when plants are subjected to different doses of N, under hydroponic conditions. The experiment was conducted in a greenhouse in nutrient solution for 20 days, with two genotypes (AS1522 and AS1596) subjected to four N concentrations (zero, 112, 224 and 448 mg dm-3). Completely randomized desing with three replications das apply. The major differences among genotypes for biometric variables, dry matter, N accumulation and free amino acids were observed in the shoots. At root, the activity of nitrate reductase activity was the variable that stood out and provided the largest differences between genotypes. The genotype AS1596 is more efficient in N utilization.